Assessing the prospect of XAFS experiments of metalloproteins under in vivo conditions at Indus-2 synchrotron facility, India - Debdutta Lahiri; Richa Agrawal; Khileshwari Chandravanshi; Parasmani Rajput; Ankur Agrawal; Ashutosh Dwivedi; Ravindra D. Makde; S. N. Jha; Nandini Garg (Journal of Synchrotron Radiation, 2023)
The feasibility of X-ray absorption fine-structure (XAFS) experiments of ultra-dilute metalloproteins under in vivo conditions (T = 300 K, pH = 7) at the BL-9 bending-magnet beamline (Indus-2) is reported, using as an example analogous synthetic Zn (0.1 mM) M1dr solution. The (Zn K-edge) XAFS of M1dr solution was measured with a four-element silicon drift detector. The first-shell fit was tested and found to be robust against statistical noise, generating reliable nearest-neighbor bond results. The results are found to be invariant between physiological and non-physiological conditions, which confirms the robust coordination chemistry of Zn with important biological implications. The scope of improving spectral quality for accommodation of higher-shell analysis is addressed.